Solutions for Mobile Devices Security Concerns, Aden Refinery Company (A.R.C) Case Study - Eng. Mohammed Badeh; Dr. Nabil Munassar (Engineering And Technology Journal, 2024)
Companies that allow their employees to use mobile devices for work purpose, they suffer from cybersecurity challenges such as virus or malware, download illegal content, poor authorization and authentication, etc. These challenges need solutions or controls to solve or mitigate them. In this paper, there are two objectives. The first aim is to know which of the security controls were asked in the questionnaire used in the A.R.C. The second objective is to know which security scenarios the IT department uses to protect the information from potential mobile device security concerns. A descriptive methodology was employed in this study. Data were collected from forty people in the IT department at Aden Refinery Company through a questionnaire. The results show that some security controls, such as antivirus/ antimalware, backups, firewalls, and policies, are used in the A.R.C.